Trifunctional cycloaliphatic epoxy-based thermoset polymers: Synthesis, polymerization, and characterization. (2nd April 2021) - Sivanesan, Dharmalingam; Seo, BongKuk; Lim, Choong-Sun; Kim, Suna; Kim, Hyeon-Gook
Abstract: High-performance thermoset materials derived from epoxy resins have excellent properties, and are widely used. Diglycidyl ether bisphenol A (DGEBA) is an extensively used monomer in the epoxy network, but despite its many advantages, its precursor, bisphenol-A, is considered toxic to human health. As an alternative to DGEBA, cycloaliphatic resins have attracted significant interest. Herein, the synthesis of trifunctional cyclohexylepoxide (CHE) and the polymerization of trifunctional cyclohexyl-epoxide with curing agents such as imidazole (IM), aliphatic, and aromatic amines are reported. The polymers are characterized using NMR spectroscopy, FT-IR, differential scanning calorimetry, and dynamic mechanical analysis. The polymer derived from CHE and IM shows different thermal stabilities based on the molar percentage of IM per epoxide. CHE/diaminodiphenylmethane (DDM) epoxy/amine thermoset shows the highest thermal mechanical stabilities. To understand and compare the polymerization of CHE with aliphatic and aromatic curing agents, the activation energies for the polymerization reactions are calculated based on the polymerization temperature at different heating rates. Further, the CHE/amine polymers are compared with the commercially available DGEBA (bifunctional epoxy) and trifunctional epoxy-containing N, N′-diglycidyl-4-glycidyloxyaniline (DGGHA) epoxy/amine polymers. Graphical abstract: Image 1 Highlights: The cycloaliphatic trifunctional epoxide synthesized and cured with imidazole, aliphatic diamines and aromatic diamines. Epoxy/amine thermoset of trifunctional epoxide with aromatic amine has the highest thermal and mechanical stability. Synthesized trifunctional epoxide has lower viscosity than the bisphenol A diglycidyl ether.